A Grounded Theory Approach to the Transformation of Railway Sites in Türkiye - Ümmü Nur Öztürk Arslan; Bahar Aktuna (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
This paper examines the obsolescence and transformation of historic railways in Türkiye, moving beyond conventional discussions of adaptive reuse. While existing research has primarily focused on the modes and strategies of repurposing disused railway buildings, this research investigates the broader processes of obsolescence, mapping the afterlives of railway heritage. It engages a grounded theory approach and systematically analyzes documents—maps, published articles, and local news—as primary data to trace how railway sites transition beyond their original function. It identifies key processes including expansion, abandonment, invisibility, and contested redevelopment and explores how ownership structures, policy shifts, and socio-political forces shape these transformation trajectories. This study situates these transformations across different historical periods, from the mid-19th century to the present, to develop a theoretical framework for understanding railway obsolescence in evolving urban, rural, and infrastructural contexts in Türkiye. The findings suggest a theory of “Relational Trajectories of Railway Heritage Transformation” and offer insights for heritage policymakers, planners, conservationists, and scholars engaged in transportation history, planning, adaptive reuse, and infrastructure conservation.